Practicality Evaluation of TPACK-Integrated Vertebrate Zoology Teaching Materials Developed Using the Plomp Model - Fauziah, Nurul; Yulis, Putri Ade Rahma; Mellisa, Mellisa; Putri, Iffa Ichwani; Erfina, Erfina; Molly, Diana; Rahmi, Ennike Gusti (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2026)
The availability of relevant, user friendly, and technology integrated teaching materials is an essential requirement in biology learning, particularly in the vertebrate zoology course. However, many learning resources are still dominated by conventional teaching materials that do not adequately integrate Technological Pedagogical Content Knowledge (TPACK) aspects. This condition may limit students' meaningful, context-rich learning experiences. This study aimed to evaluate the practicality of TPACK-integrated vertebrate zoology teaching materials in biology learning. The study employed a research and development approach using the Plomp model, focusing on the prototyping phase. Practicality evaluation was conducted through three stages: one-to-one evaluation, small group evaluation, and field testing. Data were collected using practicality questionnaires and analyzed descriptively using percentage calculations to determine the practicality category of the teaching materials. The results consistently indicated that the developed teaching materials fall within the very practical category across all evaluation stages. These findings suggest that the TPACK-integrated vertebrate zoology teaching materials are highly usable in the learning process. Therefore, the developed materials have the potential to serve as supporting learning resources in higher education biology instruction and provide a foundation for further effectiveness testing in subsequent research stages.